Analysis Of Docking Space Availability in One Web-Based Application for Shipyards In The Samarinda Region - Dewi Sartika; Muhammad Badrus Zaman; Nurhadi Siswantoro (International Journal of Marine Engineering Innovation and Research, 2023)
The development of the national shipping industry, especially shipyards, can increase the capacity of the national shipping industry in transporting goods and passengers between islands. Digitalization allows for major changes in business models that allow the creation of new companies that grow very quickly. Digitization can make new jobs easier by using technology in such a way to be used as efficiently as possible. Digitalization has created a business model that allows for a more practical concentration of the technology industry than the traditional business model. Based on information obtained in the field, shipyards in Eastern Indonesia, especially in the Samarinda and East Borneo regions, can improve the local economy, so that the schedule for the production of new building ships in the shipyard must be accommodated, upgraded to be more modern, After observations were made at several shipyards in Samarinda there appeared obstacles in the work carried out including: outsourced labor, area and waters depending on weather factors the work device still using standard technology, with these obstacles, the author tried to analyze the process of availability of shipyards in the Samarinda region using the fishbone diagram method of the purpose of the study this and all obstacles or problems faced by the shipyard through fishbone analysis and from the results of this research the result to be achieved is to make an application so that the administrative process is neat, repair and shipbuilding in the program properly and scheduled, also including repairs/maintenance, with an application-based or web-based business can help improve the business, because it will make it easier for shipowners to access adequate shipyards that are scheduled and have a location and place that suits the condition of their ships without making many long voyages to get a docking place with uncertainty of schedules.